Carbon capture technology exploitation for vanadium tailings and assessment of CO2 sequestration potential. (1st April 2023) - Huang, Jianying; Fan, Yong; Liu, Tao; Zhang, Yimin; Hu, Pengcheng
Abstract: In recent years, the global warming trend is still increasing due to CO2 emissions from various sources, such as electricity, heat production, industry, and transportation. In the vanadium industry, the vanadium bearing shale is of low grade, and the extraction of the required elemental vanadium produces large quantities of vanadium tailings (VTs). Both the roasting pretreatment of vanadium shale during vanadium extraction and the high-temperature calcination process for the preparation of vanadium products generate large amounts of CO2 gas. Therefore, it is particularly important to find an effective and environmentally friendly method for the treatment of vanadium tailings and CO2 generated by the vanadium industry. In this study, a potential method for the indirect carbonation of low calcium VTs under atmospheric pressure conditions was investigated. The carbonation reaction was investigated for different ammonia addition factors and different introduced CO2 concentrations and temperatures. The carbonation experiments showed that under the conditions of coefficient of ammonia addition of 1.4, reaction time of 60 min and reaction temperature of 60 °C, the utilization rate of calcium in VTs reached 97.9% and the CO2 uptake of VTs at 0.073 g-CO2 /g, indicating that the carbonation of vanadium with low-calcium VTs was effective. The carbonation product was analyzed and measured using TG, XRD, and SEM-EDS, and it was discovered to be CaCO3, confirming the feasibility of carbonation reaction with vanadium tailings. Furthermore, the characterization of the carbonation product confirmed the mechanism and safety of the carbonation reaction, laying the groundwork for future applications. Highlights: The application of vanadium tailings for CO2 capture and sequestration. It has higher carbon capture efficiency among other low-calcium wastes. For effective Ca, the process has a utilization rate of more than 97%.